Neurosurveillance in the workplace: do employers have the right to monitor employees' minds? - Muhl, Ekaterina; Andorno, Roberto (Frontiers in Human Dynamics, 2023)
The use of neurotechnologies for surveillance in the workplace have the potential to impact the entire working population of the world. Currently, with the help of neurodevices, employers could analyze the brain data from employees to assess their cognitive functions (such as mental capacity and efficiency), cognitive patterns (such as response to stress), and even detect neuropathologies. The workers brain data obtained with wearable neurodevices could serve employers for purposes such as promotion, hiring, or dismissal. Neurodevices could also be used as new micromanagement tools, aimed at monitoring employees' attention at work. Additionally, they can be implemented as tools for self-control for workers, as the feedback provided about their current cognitive state can help improve the outcomes of ongoing tasks and ensure safety. Recent studies have shown that while employees may recognize the potential benefits of using such technology for self-monitoring purposes, they have a negative perception towards its implementation in the workplace. Surprisingly, only a few scientific papers specifically address the issues of neurosurveillance in the workplace, while international frameworks have not yet provided precise responses to these new intrusive methods of monitoring workers. The overall goal of this paper is to discuss whether employers should be allowed to use neurosurveillance technologies in the workplace to monitor their employees' minds and, if so, under what circumstances. The authors take a hypothetical scenario of neurosurveillance in the workplace using EEG-based devices as a starting point for their analysis. On this basis, three key ethical issues are identified: an increasing power imbalance in the employment relationship; a new threat to employees' privacy, and a risk of neurodiscrimination.